2000
DOI: 10.1128/jvi.74.22.10312-10322.2000
|View full text |Cite
|
Sign up to set email alerts
|

Template Nucleotide Moieties Required for De Novo Initiation of RNA Synthesis by a Recombinant Viral RNA-Dependent RNA Polymerase

Abstract: Virology 253:1-7, 1999). Using RNAs containing nucleotide analogs, we found that the N3 and C4-amino group at the initiation cytidine were required for RNA synthesis. However, the ribose C2-hydroxyl of the initiating cytidylate can accept several modifications and retain the ability to direct synthesis. The only unacceptable modification is a protonated C2-amino group. Quite strikingly, the recognition of the functional groups for the initiation cytidylate and other template nucleotides are different. For exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 70 publications
5
26
0
2
Order By: Relevance
“…Preliminary evidence suggests that the BVDV RdRp transits to processive synthesis between the synthesis of 10-to 12-phosphodiester bonds (ref. 23 and M.-J.K., unpublished results), a value similar to that reported for the BMV replicase (33,34). The internal template switch observed with RecO may be caused by the TC not being committed to elongation by position ϩ10.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Preliminary evidence suggests that the BVDV RdRp transits to processive synthesis between the synthesis of 10-to 12-phosphodiester bonds (ref. 23 and M.-J.K., unpublished results), a value similar to that reported for the BMV replicase (33,34). The internal template switch observed with RecO may be caused by the TC not being committed to elongation by position ϩ10.…”
Section: Discussionsupporting
confidence: 70%
“…1A). Both templates lack a 5Ј phosphate but can direct de novo initiation of RNA synthesis by the BVDV RdRp (22,23). We found that (-)21-3Јdd and d(-)21 produced RNAs that are multiples of 21 nucleotides in length whose abundance increased with template concentration (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…4). For mammalian positive-strand RNA viruses such as poliovirus and hepatitis C, two mechanisms are suspected: de novo initiation (5)(6)(7)(8) and protein priming (9) from the genomic ends.…”
mentioning
confidence: 99%
“…A los elementos cis que intervienen en la replicación se les atribuyen diversas funciones, entre ellas: (1) participar en la formación de los complejos replicativos Wu et al, 2009], (2) actuar como promotores de la replicación promoviendo la síntesis de novo de la cadena complementaria [Kim et al, 2000;Kao et al, 2001], (3) regular la síntesis asimétrica de las cadenas de polaridad positiva y negativa [Ball, 2007], (4) intervenir en la transcripción de los distintos sgRNAs, si procede [Kim & Hemenway, 1999;Grdzelishvili et al, 2005] y, (5) funcionar como chaperonas de RNA [McCormack & Simon, 2004]. como mRNA permitiendo la traducción de las replicasas virales.…”
Section: Moldes Virales Requerimientos Estructurales Y De Secuenciaunclassified
“…Del mismo modo, se han intentado identificar factores del huésped potencialmente implicados en replicación utilizando técnicas de entrecruzamiento con luz UV, empleando la 5´ o 3´ UTR virales y extractos celulares. En algún caso esta estrategia ha permitido identificar proteínas con capacidad de unirse a estas secuencias reguladoras [Sriskanda et al, 1996;Kim et al, 2000], pero su efectividad ha sido, en general, limitada.…”
Section: Proteínas Auxiliares De La Replicaciónunclassified